Pengembangan model sekolah berkarakter budaya di sekolah dasar di kecamatan Ngaglik - Dwijonagoro, Suwarna; Endraswara, Suwardi; Nurhidayati, Nurhidayati (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2019)
This research aims to develop school implementation guidance based on culture bygovernment regulation no. 5 / 2011. Research and development (R & D) design useAllesi-Trollip model. Allesi-Trollip model consists of planning, designing, validating,revising, up to become a final product. Results of this research and development are (1) thisresearch was successfully developed two books : (I) Rencana Tindakan PengembanganSekolah Berbasis Budaya and (II) Contoh Implementasi Pengembangan Sekolah BerbasisBudaya nilai Sopan Santun. These books which have been assessed by experts and got the score4,36 (satisfactory). Assessment by the head of the primary school got score 4.39(satisfactory). The average of these scores is 3.38 which also means satisfactory, and (3) Themain qualitative results is SBB will soon to be socialized and implemented at elementaryschool which accompanied by Yogyakarta State University experts and supported byDikpora.